In-situ structure and catalytic mechanism of NiFe and CoFe layered double hydroxides during oxygen evolution - Fabio Dionigi (Nature Portfolio, 2020)
NiFe and CoFe layered double hydroxides are among the most active electrocatalysts for the alkaline oxygen evolution reaction. Here, by combining operando experiments and rigorous DFT calculations, the authors unravel their active phase, the reaction center and the catalytic mechanism.